Activities of daily living after surgery among older patients with gastrointestinal and hepatobiliary-pancreatic cancers: a retrospective observational study using nationwide health services utilisation data from Japan - Ayako Okuyama; Takahiro Higashi; Hisashi Kosaka; Asao Ogawa; Masaki Kaibori (BMJ Open)
Objectives The effectiveness and impact of any treatment on patients’ physical functions, especially in older patients, should be closely considered. This study aimed to evaluate activities of daily living (ADLs) after oncological surgery in patients with gastrointestinal and hepatobiliary-pancreatic cancers by age groups in Japan.Design Retrospective observational study using health services utilisation data from 1 January 2015 to 31 December 2016.Setting Data for patients with gastrointestinal and hepatobiliary-pancreatic cancers diagnosed in 2015 from 431 hospitals nationwide in Japan.Participants Patients who underwent endoscopic submucosal dissection (ESD), endoscopic mucosal resection (EMR) and laparoscopic or open surgery were included.Outcome measures The proportion of ADL decline at discharge, death and unexpected readmission within 6 weeks postsurgery was calculated by age groups (40–74, 75–79 and ≥80 years).Results Data for 68 032 patients were analysed. The difference in the proportion of ADL decline after ESD/EMR between patients aged ≥80 years and <75 years was marginal (0.8%–2.5%), whereas that after laparoscopic (4.8%–5.9%) or open surgery (4.6%–9.4%) was large, except for pancreatic cancer (3.0%). Among patients with gastric cancer who underwent laparoscopic or open surgery, the proportion of unexpected readmission tended to be higher in patients aged ≥80 years than in the remaining younger patients (laparoscopic surgery 4.8% vs 2.3% (p=0.001); open surgery 7.3% vs 4.4% (p<0.001)). The postoperative mortality rate was <3% (<10 cases) across all ages and cancer types.Conclusions In ESD/EMR, postoperative ADL decline was almost the same between older and younger patients. Laparoscopic or open surgery is associated with increased rates of ADL decline in older patients, especially in those aged ≥80 years. The potential decline in ADLs should be carefully considered preoperatively to best maintain the patient’s quality of life postsurgery.